A latent class analysis of social activities and health among community-dwelling older adults in Korea. (4th May 2018) - Park, Mi Jin; Park, Nan Sook; Chiriboga, David A.
ABSTRACT: Objectives: This study presents an empirical typology of social activity and its association with the depressive symptoms and self-rated health of community-dwelling older adults ( n = 464) in South Korea. Method: Latent class analysis (LCA) was used to classify the types of social activities. Data analyses were conducted using Mplus 7.2 program for LCA and SPSS 22.0 for multiple regression analyses. Results: LCA identified people who fell into one of the four activity groups: Diverse, Community Center/Disengaged, Religion Plus, and Friendship/Leisure. Membership in these four groups predicted differences in depressive symptoms and self-rated health. Conclusions: Results indicate that typologies of social activity could enhance practitioners' understanding of activity patterns and their associations with health and well-being.